Applied numerical methods with MATLAB for engineers and scientists - Chapra, Steven C. (McGraw-Hill, 2012)
Suitable for engineering and science students who need to learn numerical problem solving, this book introduces theory to inform key concepts which are framed in applications and demonstrated using MATLAB. It features chapters on Eigenvalues and Fourier Analysis, and is accompanied by an extensive set of m-files and instructor materials